A guide for the statistically perplexed : selected readings for clinical researchers - Streiner, David L. (University of Toronto Press, 2013)
Inspired to write on this topic in reaction to mistakes he encountered in actual papers, David L. Streiner uses his trademark sense of humour and light-hearted style to explain complex statistical concepts in lucid, jargon-free language.